Selection of Pipeline Investigation Robot via Pugh Method - Choo, Wou Onn; Yuli Panca, Asmara; Shawkat Ali, Allybocus; Adnan, Orakzai; Muhammad Izzat Nor, Ma'arof; Girma, Tadesse Chala (INTI International University, 2020)
A pipeline network or a pipeline system is the connection of several pipes that provide a path in allowing for transportation of matter. Nonetheless, failure or deterioration may occur overtime in this pipeline system due to corrosion and/erosion. Therefore, this study was aimed at determining the optimal design for a pipeline’s corrosion investigation robot via Pugh Method. An extensive research was carried out to identify the existing models and their specific mechanism for operation. Moreover, pipeline was studied to achieve a better understanding on the subject. Based on the literature, several criteria were taken into consideration in utilizing the Pugh method for the selection process. The criteria for selection were: (i) stability, (ii) mobility, (iii) adaptability, (iv) flexibility, (v) strength, and (vi) hydrodynamic. The resulting outputs were seven (7) potential designs for the corrosion investigation robot. From the Pugh Method, Design 1, Design 2, Design 3, Design 4, Design 5, Design 6, and Design 7 have earned a total of -1, +3, +2, +4, +9, +11, and +12 points respectively out of a total of +18 points. Conclusively, based on this ratings, Design 7 was selected. For future studies, it is recommended that further analysis such as finite element analysis (FEA) is conducted on Design 7.